Análisis pragmático-contrastivo de las interjecciones O polaca y Oh española - Fernández Jódar, Raúl (Studia Romanica Posnaniensia, 2025)
Interjections are fundamental elements for expressing emotions and reactions in language. This article presents a pragmatic-contrastive analysis of the interjections o in Polish and oh in Spanish, aiming to identify similarities and differences in their pragmatic use. Through a contrastive linguistics approach, various cases and usages of the aforementioned interjections will be examined, alongside the cultural and contextual implications that may lead to errors in different fields. By adopting a contrastive approach, differences in pragmatic usage will be identified, and the causes of common errors among Polish speakers of Spanish will be explored.